CD300f epitopes are specific targets for acute myeloid leukemia with monocytic differentiation - Edward Abadir; Robin E. Gasiorowski; Kaitao Lai; Fiona Kupresanin; Adelina Romano; Pablo A. Silveira; Tsun‐Ho Lo; Phillip D. Fromm; Marina L. Kennerson; Harry J. Iland; P. Joy Ho; P. Mark Hogarth; et al. (Molecular Oncology)
Antibody‐based therapy in acute myeloid leukemia (AML) has been marred by significant hematologic toxicity due to targeting of both hematopoietic stem and progenitor cells (HSPCs). Achieving greater success with therapeutic antibodies requires careful characterization of the potential target molecules on AML. One potential target is CD300f, which is an immunoregulatory molecule expressed predominantly on myeloid lineage cells. To confirm the value of CD300f as a leukemic target, we showed that CD300f antibodies bind to AML from 85% of patient samples. While one CD300f monoclonal antibody (mAb) reportedly did not bind healthy hematopoietic stem cells, transcriptomic analysis found that CD300f transcripts are expressed by healthy HSPC. Several CD300f protein isoforms exist as a result of alternative splicing. Importantly for antibody targeting, the extracellular region of CD300f can be present with or without the exon 4‐encoded sequence. This results in CD300f isoforms that are differentially bound by CD300f‐specific antibodies. Furthermore, binding of one mAb, DCR‐2, to CD300f exposes a structural epitope recognized by a second CD300f mAb, UP‐D2. Detailed analysis of publicly available transcriptomic data indicated that CD34+ HSPC expressed fewer CD300f transcripts that lacked exon 4 compared to AML with monocytic differentiation. Analysis of a small cohort of AML cells revealed that the UP‐D2 conformational binding site could be induced in cells from AML patients with monocytic differentiation but not those from other AML or HSPC. This provides the opportunity to develop an antibody‐based strategy to target AMLs with monocytic differentiation but not healthy CD34+ HSPCs. This would be a major step forward in developing effective anti‐AML therapeutic antibodies with reduced hematologic toxicity.